Study of flexural vibration of variable cross-section box-girder bridges with corrugated steel webs. (October 2021) - Shi, Fan; Wang, Dongsheng; Chen, Lei
Abstract: In this study, the flexural vibration behavior of the variable cross-section box-girder bridge with corrugated steel webs is investigated using the energy variational method in conjunction with the extended spline finite point method. Detailed equations are provided for analyzing the dynamic characteristics of simply supported girders with flexural vibration. To predict the dynamic characteristics of continuous girders with flexural vibration, the method is further expanded to incorporate the spline subdomain method. To accurately analyze the flexural frequencies and mode shapes, the stress characteristics of the corrugated steel web and the shear lag effect of the box girder are also considered. The dynamic characteristics of girders with different variable cross sections are efficiently calculated and compared by the compiled calculation program. The predicted results are in good agreement with the experimental and finite element modeling results, which proves the validity and applicability of the proposed method. The results of a parameters analysis show that increases in the variable cross-section coefficient of the girder results in increases in the flexural frequency, and lead to a change in the shape of the first mode from 'sinusoidal' to 'bell.' In addition, increases in the width-to-span ratio of the girder rapidly decrease the natural frequency, which then gradually stabilizes.